Palynology of the Chigua (Devonian) and Malimán (Carboniferous) formations in the Volcán Range, San Juan Province, Argentina. Part II. Cavate, pseudosaccate and cingulizonate spores (Ameghiniana, 2012)
Resumen. PALINOLOGÍADELASFORMACIONES CHIGUA (DEVÓNICO) Y MALIMÁN (CARBONÍFERO) ENLASIERRA DEL VOLCÁN, PROVINCIADE SAN JUAN, ARGENTINA. PARTE II. ESPORASCAVADAS, PSEUDOSACADASYCINGULI- ZONADAS.Se presenta el análisis sistemático de las asociaciones palinológicas obtenidas de sedimentitas de las formaciones Chigua y Malimán, Devónico medio y Mississippiano respectivamente, aflorantes en la sierra del Volcán, cuenca Río Blanco, oeste de Argentina. En esta segunda parte se ilustran 40 especies de esporas cavadas, pseudosacadas y cingulizonadas presentes en ambas formaciones. La especie Geminospora sp. cf. G.tuberculata var. tuberculata McGregor es registrada por primera vez en el Devónico medio de América del Sur. Las siguientes especies también son registradas por primera vez para el Mississippiano de América del Sur, Crassisporainvicta Playford, Densosporitesasperus Braman y Hills, Densosporitesgracilis Smith y Butterworth, Densosporitessecundus Playford y Satterthwait, Densosporites sp. cf. D.triangularis Kosanke, Gorgonispora sp. cf. G.crassa (Winslow) Higgs etal., Lophozonotriletesdentatus Hughes and Playford, Spelaeotriletesechinatus (Hacquebard) Utting, Velamisporitesperinatus (Hughes y Playford) Playford. Se ilustran y en algunos casos se describen algunas especies (escolecodontes, paleomicroplancton y esporas) posiblemente retrabajadas presentes en la Formación Malimán.Abstract. Palynological analysis of the Chigua and Malimán formations of Middle Devonian and Mississippian age respectively, is presented. They crop out in the Del Volcán Range at the Río Blanco Basin in western Argentina. In this second part, 40 indigenous species of cavate, pseudosaccate and cin- gulizonate spores from both units are illustrated. The species Geminospora sp. cf. G.tuberculata var. tuberculata McGregor is recorded in the Middle Devonian of South America for the first time. The following species are also recorded in the Mississippian of South America for the first time as Crassisporainvicta Playford, Densosporitesasperus Braman and Hills, Densosporitesgracilis Smith and Butterworth, Densosporitessecundus Playford and Satterthwait, Densosporites sp. cf. D.triangularis Kosanke, Gorgonispora sp. cf. G.crassa (Winslow) Higgs etal., Lophozonotriletesdentatus Hughes and Playford, Spelaeotriletesechi- natus (Hacquebard) Utting, Velamisporitesperinatus (Hughes and Playford) Playford. Some possibly re- worked species (scolecodonts, paleomicroplankton and spores) from the Malimán Formation are illustrated and some of them are also described.